Introduction to solid state physics - Kittel, Charles (Wiley, 2018)
Using the simplifications made possible by the availability of computer technology, this is a solid state physics text for physics students. It emphasises on physics rather than formal mathematics. It attempts to add important developments in the field without sacrificing the book's accessibility and teachability.